2023
DOI: 10.3390/jpm13010157
|View full text |Cite
|
Sign up to set email alerts
|

Potential Therapies Targeting the Metabolic Reprogramming of Diabetes-Associated Breast Cancer

Abstract: In recent years, diabetes-associated breast cancer has become a significant clinical challenge. Diabetes is not only a risk factor for breast cancer but also worsens its prognosis. Patients with diabetes usually show hyperglycemia and hyperinsulinemia, which are accompanied by different glucose, protein, and lipid metabolism disorders. Metabolic abnormalities observed in diabetes can induce the occurrence and development of breast cancer. The changes in substrate availability and hormone environment not only c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 153 publications
0
7
0
Order By: Relevance
“…46 It can inhibit cell division in the G2/M phase and reduces tumor development by modulating the miR-21 gene in HCT-116 cells. 47 Several studies observed that curcumin inhibits the JAK/STAT signaling by significantly reducing the phosphorylation of JAK2 and STAT3 levels in CRC cells 48,49 Curcumin (2 g/day) and chemotherapeutic drugs were synergistically administered in 27 CRC patients during clinical trial.…”
Section: Colon Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…46 It can inhibit cell division in the G2/M phase and reduces tumor development by modulating the miR-21 gene in HCT-116 cells. 47 Several studies observed that curcumin inhibits the JAK/STAT signaling by significantly reducing the phosphorylation of JAK2 and STAT3 levels in CRC cells 48,49 Curcumin (2 g/day) and chemotherapeutic drugs were synergistically administered in 27 CRC patients during clinical trial.…”
Section: Colon Cancermentioning
confidence: 99%
“…It can inhibit cell division in the G2/M phase and reduces tumor development by modulating the miR‐21 gene in HCT‐116 cells 47 . Several studies observed that curcumin inhibits the JAK/STAT signaling by significantly reducing the phosphorylation of JAK2 and STAT3 levels in CRC cells 48,49 Curcumin (2 g/day) and chemotherapeutic drugs were synergistically administered in 27 CRC patients during clinical trial. Curcumin (2 g/day) was found to be safe and tolerable, increasing patients' overall survival and response rate when administered with chemotherapeutic drugs in 27 CRC patients during clinical trial 50 …”
Section: Antiproliferative/anticancer Activities Of Curcuminmentioning
confidence: 99%
“…Diabetes is one example where combination therapy between immunotherapy and metabolic intervention can be employed to better realize the potential of anticancer therapy. More and more evidence shows that abnormal metabolism in diabetes not only plays a key role in maintaining cancer signals of tumor occurrence and survival but also has a wider significance in regulating the anti-tumor immune response by releasing metabolites and influencing the expression of immune molecules, for instance, lactic acid and arginine [312].…”
Section: Brown Adipose Tissue (Bat)mentioning
confidence: 99%
“…More research on these aspects is necessary to enhance treatment options for breast cancer in patients with diabetes. 88 In general, having advanced illness discovered in women with diabetes at the time of breast cancer diagnosis has a minor but considerable negative impact, and this may contribute to other disparities in the treatment route that may have an effect on patient outcomes. 89 The risk of breast cancer increases with diabetes.…”
Section: Breast Cancermentioning
confidence: 99%
“…Most preclinical research focuses on reprogramming glucose metabolism, while little attention has been paid to the metabolism of lipids and amino acids. More research on these aspects is necessary to enhance treatment options for breast cancer in patients with diabetes 88 . In general, having advanced illness discovered in women with diabetes at the time of breast cancer diagnosis has a minor but considerable negative impact, and this may contribute to other disparities in the treatment route that may have an effect on patient outcomes 89 .…”
Section: Diabetes As Cancer Promotermentioning
confidence: 99%